Effectiveness and challenges of agricultural extension in Maros district: Analysis of approaches and methods - Sumandiyar, Adi; Nur, Hasruddin; Rizal, Andi (Edelweiss Applied Science and Technology, 2025)
Community empowerment is essential in building an institutional system that allows individuals or community groups to achieve progress, prosperity, and independence. This study examines the role of agricultural extension in empowering rice farmer groups in Maros Regency, focusing on efforts to improve farmers' social welfare. Agricultural extension in this area plays a vital role in developing farmer capacity. However, its effectiveness is still influenced by the ability of extension workers to adjust delivery methods to local needs. This study uses a qualitative descriptive approach designed to provide a comprehensive and in-depth picture of the phenomenon being studied. Data were collected through triangulation, which involved three main techniques: documentation studies, in-depth interviews, and observations. The study results revealed that the group socialization method has helped reach many farmers, but there are challenges in ensuring that all farmers understand and can adopt new technologies effectively. To overcome this challenge, a more adaptive and personalized approach is recommended, such as individual visits and additional, more practical training, to ensure that extension can significantly improve farmer productivity and welfare. This study emphasizes the importance of regular evaluation of the extension methods used to adjust to farmers' needs and feedback to realize sustainable empowerment.